2011
DOI: 10.1504/ijicot.2011.044677
|View full text |Cite
|
Sign up to set email alerts
|

Minimising delay for video conference with network coding

Abstract: Video conference is an attractive and promising application which allows immersive communication and discussion among people at different and distant places. However, its stringent delay and bandwidth requirements limit its scale and spread over current internet. This paper attempts to introduce the prosperous technology of network coding (NC) into video conference to minimise the maximal transmission delay between source and all the participants while retaining high bandwidth utilisation at the same time. Ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In , Costa et al proposed several algorithms to minimize the decoding delay and showed that a greedy algorithm significantly outperforms existing NC‐based protocols. For the attractive video conference applications with stringent delay and bandwidth requirements, in , Zhang et al introduced a NC algorithm for video conferencing systems to minimize the maximal transmission delay during multicast while retaining high throughput. To minimize decoding delay, in , Sadeghi et al cast the problem of instantly decodable NC as an integer linear program and proposed several efficient algorithms to solve it heuristically.…”
Section: Related Workmentioning
confidence: 99%
“…In , Costa et al proposed several algorithms to minimize the decoding delay and showed that a greedy algorithm significantly outperforms existing NC‐based protocols. For the attractive video conference applications with stringent delay and bandwidth requirements, in , Zhang et al introduced a NC algorithm for video conferencing systems to minimize the maximal transmission delay during multicast while retaining high throughput. To minimize decoding delay, in , Sadeghi et al cast the problem of instantly decodable NC as an integer linear program and proposed several efficient algorithms to solve it heuristically.…”
Section: Related Workmentioning
confidence: 99%
“…To increase throughput and improve error resilience, NC has been recently suggested for applications in multimedia streaming [10][11][12][13][14], and in particular, for multi-user video conferencing [15][16][17]. In [15], which is closest to our work, RLC is investigated for multi-party video conferencing in wireless broadband cellular systems.…”
Section: Introductionmentioning
confidence: 99%
“…In [48], when minimizing the required coding operations, we make sure that the constructed multicast session meets the delay constraint. Zhang et al present a network coding algorithm for video conferencing systems, where the maximum transmission delay is minimized while high throughput is retained [50]. In [8], the problem of efficiently placing network coding nodes in overlay networks is concerned so as to keep a high data transmission rate and low delivery latency.…”
mentioning
confidence: 99%